Influnce of Corporate Governance on Financial Health of Nepalese Commercial Banks - Bhandari, Mohan; Ranabhat, Manisha (Journal of Interdisciplinary Studies, 2021)
This study aims to measure the impact of corporate governance on financial health of commercial banks in Nepal. Return on assets, return on equity and earnings per share are the dependent variables used to measure financial health and corporate governance variables such as board size, audit committee size, audit committee meetings and board diligence are considered as independent variables. Primary and secondary data were collected through the administration of structured questionnaire and from the annual reports of commercial banks respectively. Convenience sampling was used to select the commercial banks located in Pokhara valley for collecting primary data. Simple random sampling was used to select 10 commercial banks (5 joint venture and 5 non joint venture banks) out of total population of 27 commercial banks for a time period of 2017/18 to 2019/20 for collecting secondary data. Multiple regression analysis and descriptive statistics were used in analyzing the data. Independent sample t-test was used to test the hypothesis in order to find out the relationship between corporate governance and financial performance. The questionnaire survey reveals that board independence and audit committee independence are the most important variable for corporate governance. The primary data analysis concluded that small size board enhances the financial health. Transparency and disclosure is also an important feature of audit committee mechanisms. The analysis of secondary data reveals that audit committee meetings has a significant but inverse relationship with health of the commercial banks. The result indicates that priority should be given for quality of meetings but not the number of times such meetings are held due to the busyness of directors having better knowledge, expertise and their involvement in different sectors. The results support the idea that board busyness is useful factor for director quality. And busyness needs to be integrated with diligence to the extent that busy directors are diligent towards firms and they are able to exercise their expertise to positively influence firm performance. This study also helps the future researchers to conduct future research on impact of corporate governance on financial health to extend with new data and huge sample.